PENGARUH DISIPLIN KERJA DAN ROTASI JABATAN TERHADAP PRODUKTIFITAS KERJA KARYAWAN PADA PT. MITRA BETON MANDIRI PROYEK BENDUNGAN TIGADIHAJI OKU SELATAN - Virdianto, Riki; Veronica Priharti, Rr. Dimas; Dona, Eka Meiliya (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
The purpose of this study is to determine the effect of work discipline and job rotation on employee productivity at PT. Mitra Beton Mandiri, Tigadihaji Dam Project, OKU Selatan. The analysis method used is quantitative. The study employs multiple linear regression analysis. The partial analysis results indicate that work discipline (X1) significantly influences employee productivity (Y), as evidenced by a t-value of 2.424 > t-table of 2.052. Similarly, job rotation (X2) significantly influences employee productivity (Y), with a t-value of 3.006 > t-table of 2.052. Simultaneously, work discipline and job rotation significantly influence employee productivity at PT. Mitra Beton Mandiri, as indicated by an F-value of 36.955 > F-table of 3.35. The coefficient of determination (RÂ²) is 0.732, indicating that work discipline and job rotation contribute 73.2% to employee productivity, while the remaining 26.8% is influenced by other variables not examined in this study.